2016
DOI: 10.1007/s00425-016-2505-7
|View full text |Cite
|
Sign up to set email alerts
|

miR393 contributes to the embryogenic transition induced in vitro in Arabidopsis via the modification of the tissue sensitivity to auxin treatment

Abstract: Main conclusionmiR393 was found to control embryogenic transition in somatic cells in Arabidopsis via control of theTIR1andAFB2auxin receptors genes of the F-box family.miR393 molecules are believed to regulate the expression of the auxin receptors of the TAAR clade. Considering the central role of auxin in the induction of somatic embryogenesis (SE) in plant explants cultured in vitro, the involvement of miR393 in the embryogenic transition of somatic cells has been hypothesised. To verify this assumption, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 64 publications
(89 reference statements)
3
57
0
3
Order By: Relevance
“…The expression of different MIRNA gene family members is strictly regulated during plant development in an organ-and tissue-specific manner [80,81], and thus reporter line analyses could be important in identifying the specific MIRNA genes that contribute to SE induction. Accordingly, the expression of MIR167c, MIR393a,b, and MIR396b have been found to colocalize with the SE-induction sites of the explants, which supports the contribution of these genes to miRNA-mediated regulation of SE [56,82,83]. However, most of the reporter lines monitor the gene promoter activity rather than localize the corresponding gene transcript.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 76%
See 2 more Smart Citations
“…The expression of different MIRNA gene family members is strictly regulated during plant development in an organ-and tissue-specific manner [80,81], and thus reporter line analyses could be important in identifying the specific MIRNA genes that contribute to SE induction. Accordingly, the expression of MIR167c, MIR393a,b, and MIR396b have been found to colocalize with the SE-induction sites of the explants, which supports the contribution of these genes to miRNA-mediated regulation of SE [56,82,83]. However, most of the reporter lines monitor the gene promoter activity rather than localize the corresponding gene transcript.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 76%
“…Extensive modulation of the TF genes in an embryogenic culture of Arabidopsis is accompanied by differential expression of numerous miRNAs, suggesting the function of miRNA-regulation in the embryogenic transition of plant somatic cells [54,55]. In support, the dcl1 mutant, a defect in the DICERLIKE1 (DCL1) gene with a key role in miRNA biogenesis, was shown to be unable for SE induction [56]. In addition to Arabidopsis, numerous miRNAs with a differential expression have been identified in embryogenic cultures of different gymnosperm, mono-and dicot plants, including economically important species .…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, miR393 , which plays a key role in auxin signaling during plant development, was identified (Navarro et al, 2006; Si-Ammour et al, 2011). A recent report on SE in Arabidopsis confirmed that miR393 contributes to embryogenic transition by targeting the auxin receptors, TIR1 and AFB2 , and modulating tissue sensitivity to auxin treatment (Wójcik and Gaj, 2016). Another auxin signaling-related miRNA candidate, miR160 , was indicated as controlling the development of various organs in Arabidopsis, particularly zygotic embryos, by targeting ARF10, ARF16 , and ARF17 (Liu et al, 2007; Liu and Chen, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, to fully understand the function of DNA methylation in the embryogenic transition the functional outcome of DNA methylation in the context of other epigenetic changes remains to be uncovered. Moreover, it is of importance to reveal the relation of DNA methylation with the recently identified miRNA that plays a regulatory role in the SE of Arabidopsis (Wójcik and Gaj 2016;Szyrajew et al 2017;Wójcik et al 2017). …”
Section: Discussionmentioning
confidence: 99%